Necessity of genetic diversity study and conservation practices in chironji (Buchanania cochinchinensis (Lour.) M.R. Almedia) - Ayushman Malakar; Hareram Sahoo; Animesh Sinha; Aditya Kumar (Environment Conservation Journal, 2023)
Chironji (Buchanania cochinchinensis) is an indigenous tree species of Indian subcontinent which belongs to the Anacardiaceae family. It has tremendous potential to uplift the socio-economic status of village dwellers and tribal people. It is used for various purposes including fruits, fuel, fodder and medicines. The species is facing severe ecological and anthropogenic pressures due to indiscriminate harvesting and illicit felling. IUCN has designated Chironji as a vulnerable species indicating that it may be on the verge of extinction if proper conservation measures are not taken very soon. The reports on its conservation and genetic improvement are very less. Hence, it is needed to devise the strategies to conserve its germplasm and genetically improve the species for higher fruit yield. The genetic diversity present in the species is also needed to be studied for effective conservation. Eco-distribution mapping and Molecular characterization using modern tools like molecular markers can give an accurate idea about the genetic diversity in lesser time and will also help in devising the breeding strategies and conservation of its diverse genotype. This review encompasses the researches done on Chironji till date detailing the importance of its genetic diversity and tries to indicate the future conservation and improvement strategies to be taken to fill up the remaining gaps.